2021
DOI: 10.3390/biomedicines9040418
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Methods in the Evaluation of Atherosclerosis: From Pathophysiology to Clinic

Abstract: Atherosclerosis is a key pathological process that causes a plethora of pathologies, including coronary artery disease, peripheral artery disease, and ischemic stroke. The silent progression of the atherosclerotic disease prompts for new surveillance tools that can visualize, characterize, and provide a risk evaluation of the atherosclerotic plaque. Conventional ultrasound methods—bright (B)-mode US plus Doppler mode—provide a rapid, cost-efficient way to visualize an established plaque and give a rapid risk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 151 publications
0
25
0
Order By: Relevance
“…We have performed a shotgun proteomic analysis on highly purified HDL and LDL fractions from pooled plasma samples obtained through two ultracentrifugation steps in high-salt media from patients who underwent carotid endarterectomy and healthy controls, which allowed for the comparison of levels of tens of proteins simultaneously. Plasma samples from patients were pooled according to carotid plaque echogenicity using ultrasonography, a well-established non-invasive method to assess plaque characteristics and the severity of carotid stenosis [ 39 , 40 , 41 , 42 , 43 ]. The use of pooled samples represents the major limitation of the present study since each piece of data reported represents an average value while a measurement of the level of variation or dispersion from the average is missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have performed a shotgun proteomic analysis on highly purified HDL and LDL fractions from pooled plasma samples obtained through two ultracentrifugation steps in high-salt media from patients who underwent carotid endarterectomy and healthy controls, which allowed for the comparison of levels of tens of proteins simultaneously. Plasma samples from patients were pooled according to carotid plaque echogenicity using ultrasonography, a well-established non-invasive method to assess plaque characteristics and the severity of carotid stenosis [ 39 , 40 , 41 , 42 , 43 ]. The use of pooled samples represents the major limitation of the present study since each piece of data reported represents an average value while a measurement of the level of variation or dispersion from the average is missing.…”
Section: Discussionmentioning
confidence: 99%
“…Plaques were classified according to Gray-Weale classification [ 38 ] into five types: uniformly echolucent plaque (type 1), predominantly echolucent plaque with <50% echogenic areas (type 2), predominantly echogenic plaque with <50% echolucent areas (type 3), uniformly echogenic plaque (type 4), and plaque with heavy calcification and acoustic shadows (type 5). This method represents an effective and non-invasive way to detect and characterize atherosclerotic plaque in peripheral arteries and provides a rapid risk stratification of the patient through the Gray-Weale standardization [ 39 , 40 , 41 , 42 ]. Patients were sorted, according to the plaque typology, into “soft” ( n = 44), having a carotid plaque with hypoechoic features (types 1 and 2), and “hard” ( n = 31), having a carotid plaque with hyperechoic features (types 3, 4, and 5).…”
Section: Methodsmentioning
confidence: 99%
“…Conventional ultrasound is a non-invasive, rapid, and convenient method. It can be repeated many times and has a wide range of applicability ( 13 ). Contrast-enhanced ultrasound (CEUS) is a non-invasive method developed using conventional ultrasound technology as a foundation that provides more information, better image quality, and more quantitative data through intravenous injection of contrast agent as tracer ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be repeated many times and has a wide range of applicability ( 13 ). Contrast-enhanced ultrasound (CEUS) is a non-invasive method developed using conventional ultrasound technology as a foundation that provides more information, better image quality, and more quantitative data through intravenous injection of contrast agent as tracer ( 13 ). CEUS can clearly show conditions in the lumen, such as whether there is a contrast filling defect, and evaluate the degree of thrombus formation in the lumen.…”
Section: Introductionmentioning
confidence: 99%
“…The current ultrasound methods for visualization and risk evaluation of atherosclerotic plaques are reviewed in detail [ 23 ].…”
mentioning
confidence: 99%